Effects of protein skimming on water quality, bacterial abundance and abalone growth in land based recirculating aquaculture systems - Rahman, Mohammad Mustafizur; Kadowaki, Shusaku; Linn, Saw Mya; Yamada , Yohei (Academic Journals, 2012)
Recirculating aquaculture systems can reduce many challenges associated with open culture systems but maintaining suitable water quality in recirculating system is difficult. Protein skimmer removes organic matter from the water before it breaks down into nitrogenous waste. Therefore, the aim of this study was to evaluate the effects of protein skimming on water quality, bacterial abundance and abalone growth in recirculating aquaculture system. Two recirculating systems utilizing artificial seawater were housed in an air-conditioned, insulated recycle frozen container (4.3×1.9×1.9 m) to maintain optimum water temperature (19.2  0.80C) for abalone growth. Each system consisted of two biofilters (100 and 200 L) and two abalone culture tanks (each 200 L) containing three plastic baskets (each 50 × 34 × 6 cm, with 12 mm mesh). One culture system incorporated a protein skimmer. Over an experimental period of 87 days, protein skimming resulted in significantly better water quality, heterotrophic bacterial abundance and abalone growth. Results indicate recirculating abalone culture systems with protein skimmer housed in an air-conditioned, insulated recycle frozen container may provide a viable alternative to current land-based, flow-through systems. More research is needed to further increase the efficiency of this system.